The shape of drama therapy in South Africa: trends in research and practice - Mayson, Jessica (My University, 2021)
This research maps the shape of drama therapy in South Africa, describing the trends in research and practice. The intention is to position drama therapy so as to best provide effective mental healthcare within the challenging contexts of South Africa. This objective is accomplished through a mixed methods design, which allows for the trends in drama therapy research and practice to be tracked. From these trends, an integrated and critical discussion presents the shape that drama therapy has taken in South Africa. In Chapter One, following the exploration of the reality of mental healthcare provision in South Africa and the challenges of providing therapy in diversity, a brief description of drama therapy as found and developed in South Africa is provided. In Chapter Two, international evidence is presented that demonstrates that the longevity of drama therapy provision depends on the critical reflexivity and documentation of its theoretical orientations and methods. The necessity of exploring drama therapy within diverse contexts is further explored through relevant literature. Chapter Three states the research design, and methods of data collection (a systematic literature review and an online questionnaire) and data analysis (a systematic literature review, qualitative content analysis and quantitative analyses). Chapter Four presents the results of these analyses, and Chapter Five describes the trends in drama therapy research and practice in South Africa. In addition, this chapter contains a critical discussion that uses these trends to explore the strengths, surprises, and places in need of attention in the shape of drama therapy in South Africa. Chapter Six concludes the report by weaving the chapters together and presenting the implications for the future of drama therapy in South Africa. This research identifies several findings, including: the need to build the drama therapy research field so best practice and advocacy may be increased, the responsibility of drama therapists to be involved in existing arts therapies structures, the need for South African drama therapy training to align itself with the realities of this therapy practice in this context, and the urgent need to increase diversity within the profession. In many ways, these issues prompt more questions than answers. However, if they are addressed, these discoveries can aid the research and practice of drama therapy in South Africa to best serve the many who are seeking mental health care in this country.
Research report submitted to the Wits School of Arts (Drama for Life Department) at the University of the Witwatersrand’s Faculty of Humanities, in partial fulfilment of the requirements for the degree of Master of Arts in Drama Therapy, 2021